2016
DOI: 10.1002/mds.26878
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human assessment of PRX002, an anti-α-synuclein monoclonal antibody, in healthy volunteers

Abstract: Background: α‐Synuclein is a major component of pathologic inclusions that characterize Parkinson's disease. PRX002 is an antibody that targets α‐synuclein, and its murine parent antibody 9E4 has been shown in preclinical studies to reduce α‐synuclein pathology and to protect against cognitive and motor deteriorations and progressive neurodegeneration in human α‐synuclein transgenic mice. Methods: This first‐in‐human, randomized, double‐blind, placebo‐controlled, phase 1 study assessed the impact of PRX002 adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
154
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(176 citation statements)
references
References 37 publications
2
154
0
3
Order By: Relevance
“…At present, two main antibodies targeting α‐syn have been tested in clinical trials: BIIB054 and PRX002 . The first one is an aggregate‐selective human‐α‐syn‐derived antibody, which could ameliorate disease phenotype in mouse models of synucleinopathy .…”
Section: The Possible Approaches To Directly Target α‐Syn Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…At present, two main antibodies targeting α‐syn have been tested in clinical trials: BIIB054 and PRX002 . The first one is an aggregate‐selective human‐α‐syn‐derived antibody, which could ameliorate disease phenotype in mouse models of synucleinopathy .…”
Section: The Possible Approaches To Directly Target α‐Syn Pathologymentioning
confidence: 99%
“…It has been found that BIIB054 possesses favorable safety, tolerability, and pharmacokinetic profiles in volunteers and moderate PD (Hoehn and Yahr stage ≤2.5, and time since PD diagnosis ≤5 years) patients . The second, PRX002, is derived from the murine monoclonal antibody 9E4 and preferentially targets soluble and insoluble aggregated forms of α‐syn . In a first Phase 1 study, it showed efficient serum α‐syn binding ability as well as favorable safety, tolerability, and pharmacokinetic profiles at all doses tested, with no immunogenicity .…”
Section: The Possible Approaches To Directly Target α‐Syn Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Early imaging of α-syn load will be important in disease-modifying LBD and MSA therapeutic trials. Anti-synuclein clinical trials are currently underway and are aimed at slowing down or reversing neurodegenerative damage caused by oligomeric or fibrillar α-syn species (240, 241). As the AD therapy community has learned, it will be important to accurately diagnose and identify α-syn patients for early treatment.…”
Section: α-Synucleinopathiesmentioning
confidence: 99%
“…An α-syn passive immunotherapy approach using a humanized monoclonal antibody against α-syn (Prothena, PRX002) has also been tested in Phase Ia and Ib clinical trials. In both trials, free serum α-syn levels were drastically reduced (Schenk et al, 2017). A dose-dependent increase in PRX002 levels in cerebrospinal fluid was observed, without serious adverse events.…”
Section: Therapeutic Opportunities Based On the Msa Neuropathologymentioning
confidence: 99%